IMPLEMENTASI MODEL PEMBELAJARAN PJBL DALAM PEMBELAJARAN PANTUN: ANALISIS PERUBAHAN DAN DAMPAKNYA BAGI SISWA KELAS V - Manalu, Ermawiyah B.; Marjo, Happy Karlina (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
The problem addressed in this study is the low levels of student activeness, creativity, initiative, self-confidence, and critical thinking skills in learning pantun through conventional methods. To overcome this, the Project-Based Learning (PjBL) model was implemented as a student-centered and context-based learning approach. The novelty of this study lies in the integration of PjBL with pantun learning through a final product in the form of a local wisdom-themed sociodrama, along with the use of Canva for digital presentation—an approach rarely applied at the elementary school level. This research employed a descriptive qualitative method with data collected through observation, interviews, questionnaires, and documentation of formative and summative assessments. PjBL was carried out in three stages: identifying pantun elements, composing pantun in the form of a sociodrama, and presenting the results digitally. The findings indicate improvements in student engagement, creative thinking, initiative, and self-confidence. Critical thinking skills also developed through group collaboration and decision-making processes. Quantitatively, students’ average formative test score reached 82.48, and the summative score reached 92.85, showing a significant increase in understanding and skills. In conclusion, PjBL supported by digital media is effective in improving the quality of pantun learning and is relevant for fostering students’ holistic and contextual competencies